Low sensitivity of three-phase bone scintigraphy for the diagnosis of repetitive strain injury - Amorim, Bárbara Juarez (2006)
CONTEXT AND OBJECTIVE: The diagnosis of repetitive strain injury (RSI) is subjective and solely based on clinical signs and physical ex- amination. The aim of this paper was to assess the usefulness of three-phase bone scintigraphy (TPBS) in diagnosing RSI. DESIGN AND SETTING: Prospective study at the Division of Nuclear Medicine, Department of Radiology, School of Medical Sciences, Univer- sidade Estadual de Campinas (Unicamp). METHODS: Seventy-three patients (mean age 31.2 years; 47 males) with clinical suspicion of RSI in the upper limbs were studied. A total of 127 joints with suspicion of RSI were studied. The shoulders, elbows and wrists were ana- lyzed semi-quantitatively, using the shafts of the humeri and ulnae as references. The results were compared with a control group of 40 normal individuals. The patients’ signs and symptoms were used as the “gold standard” for calculating the probabilities. RESULTS: From visual analysis, abnormalities were observed in the flow phase for four joints, in the blood pool phase for 11 joints and in the delayed images for 26 joints. Visual analysis of the joints of the control group did not show any abnormalities. Semi-quantitative analysis showed that most of the patients’ joint ratios were normal. The exceptions were the wrists of patients with left-sided RSI (p = 0.0216). However, the sensitiv- ity (9%) and accuracy (41%) were very low. CONCLUSION: TPBS with semi-quantitative analysis has very low sensitivity and accuracy in the detection of RSI abnormalities in the up- per limbs.